The Determinants of Firm Value: Commodity Prices, Exchange Rates, Inflation, and Business Risk as Intervening Variable - Nugraheni, Pristina; Risman, Asep (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Purpose – The objective of this study is to examine The Determinants of Firm Value: Commodity Prices, Exchange Rates, Inflation, and Business Risk as Intervening Variable. The population in this study consists of the mining sector and plantation sub-sector companies listed on the Indonesia Stock Exchange from 2017 to 2022. Methodology/approach – The sampling technique used is purposive sampling, resulting in a total of 31 research samples used in this study. The data analysis techniques employed in this research are panel data regression and the Sobel test. Findings – The analysis results indicate that Commodity Prices and Exchange Rate have a significant negative effect on Firm Value; Inflation does not affect Company Value and Business Risk has a significant positive effect on Firm Value; Commodity Prices and Exchange Rate have a significant positive effect on Business Risk; and Inflation does not effect on Business Risk; Business Risk can mediate the effect of Commodity Prices and Exchange Rate on Firm Value; and Business Risk is not able to mediate the effect of Inflation on Firm Value.